Metaheuristics for Scheduling in Industrial and Manufacturing Applications - Xhafa, Fatos; Abraham, Ajith (Studies in Computational Intelligence, 2008)
During the past decades scheduling has been among the most studied optimization problems and it is still an active area of research! Scheduling appears in many areas of science, engineering and industry and takes different forms depending on the restrictions and optimization criteria of the operating environments. This book deals with the application of various novel metaheuristics in scheduling. Addressing the various issues of scheduling in industrial and manufacturing applications is the novelty of this edited volume. Important features include the detailed overview of the various novel metaheuristic scheduling approaches, excellent coverage of timely, advanced scheduling topics, state-of-the-art theoretical research and application developments and chapters authored by pioneers in the field. Academics, scientists as well as engineers engaged in research, development and scheduling will find the comprehensive coverage of this book invaluable